A Note on Good Practice of Objective Propensity Score Design for Premarket Nonrandomized Medical Device Studies with an Example. (2nd July 2016) - Li, Heng; Mukhi, Vandana; Lu, Nelson; Xu, Yun-Ling; Yue, Lilly Q.
ABSTRACT: In this short note, we highlight some key elements of the process of submitting an investigational device exemption of a nonrandomized clinical study that involves the use of propensity score methodology. Focus is given to the assessment of balance for propensity score stratification.